Skrining Fitokimia dan Uji Aktivitas Antioksidan Ekstrak Etanol Daun Ciplukan (Physalis angulata L) Dikawasan Manifestasi Geothermal Seulawah Agam - Farida , Mutia; Azhari , Saiful; Darsa , Dimas Dwi; Mahmudi , Mahmudi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Ciplukan leaves (Physalis angulata L.) from the Seulawah Agam geothermal manifestation area exhibit strong potential as a natural antioxidant source. This study investigates the phytochemical content and antioxidant activity of ethanol extract from ciplukan leaves using UV-Vis spectrophotometry. The research begins with sample collection and plant determination, followed by phytochemical screening and antioxidant activity testing using the DPPH method. Phytochemical screening results reveal the presence of alkaloids, flavonoids, tannins, saponins, and steroids. Antioxidant activity testing using the DPPH method yields an IC50 value of 14.99 μg/mL, significantly lower than the positive control, ascorbic acid (19.40 μg/mL), indicating strong antioxidant activity. At the highest tested concentration (50 μg/mL), the extract exhibits an inhibition percentage of 81.84%, while at the lowest concentration (10 μg/mL), it shows an inhibition of 41.41%. These findings confirm that the ethanol extract of ciplukan leaves from the geothermal area possesses high antioxidant content and has great potential for applications in the development of natural-based pharmaceutical and nutraceutical products.